The intervention of rehabilitation nurses in elderly patients with proximal femur fracture - Fernandes, Andrea (2016)
The rehabilitation nurse plays a key role in promoting and maintaining the health of the elderly, guided by direct assistance at various levels of complexity, complexity, where the elderly/family/community has its role preserved, and the main goal is that the elderly regain their functional independence as early as possible. The aim of this study is to evaluate the functional independence of the elderly with proximal femur fracture with the intervention of rehabilitation nurse.